Analysis of Essential Oil Compounds from Eucalyptus (Eucalyptus pellita) Leaves and Their Bioactivity Against Staphylococcus aureus - Alam, Rizki Nur; Supriadin, Asep; Kurniasih, Nunung (Walisongo Journal of Chemistry, 2024)
Eucalyptus (Eucalyptus pellita) is a plant commonly found in Garut Regency, Indonesia, with its leaves showing potential for essential oil extraction. Hence, this study aimed to determine the yield, analyze the chemical composition, and evaluate the bioactivity of essential oils derived from Eucalyptus pellita leaves against Staphylococcus aureus. The essential oil was extracted utilizing Stahl distillation from leaves collected in Cisarua Village, Samarang District, Garut Regency. The chemical composition was identified through Gas Chromatography-Mass Spectrometry (GC-MS), and its antibacterial activity against S. aureus was assessed using the disc diffusion method. As a result, the average essential oil yield was 0.34%, with compounds identified as α-phellandrene (3.20%), α-terpineol (5.52%), γ-terpinene (7.07%), 1,8-cineole (7.26%), α-terpinyl acetate (13.40%), and limonene (50.47%). The bioactivity test results indicated that the inhibition zone diameter at a 25% concentration of essential oil was categorized as moderate, while concentrations of 50% and 100% demonstrated strong antibacterial activity.